Character Education for Adults: A Phenomenological Overview of Future Social Realities - Lutfi, Saiful; Erawati, Desi (Riwayat: Educational Journal of History and Humanities, 2025)
While character education has focused on children and adolescents, adults also face complex moral challenges. This study aims to understand how adults shape and strengthen their character amidst social, technological and value changes. Using a phenomenological qualitative approach, data was collected through in-depth interviews with 12 adult participants from various professions, and analysed using Moustakas' (1994) stages. The results showed that character in adults is a dynamic process influenced by critical reflection on life experiences, as well as adaptation to changing social contexts. The social environment and community proved to be an important space for authentic value learning, providing dialog, social practice, and spiritual reinforcement. Despite facing dissonance between personal values and social norms, participants showed hope for character transformation through open dialog and community support. This research concludes that adult character education needs to be reflective, participatory and community-based, and offers a model of character learning that is relevant for adult individuals as adaptive and critical moral agents in modern society.